Southeast Asian Affairs (JSTOR)
Southeast Asian Affairs, which has been produced since 1974, is an annual review of significant trends and developments in the region. The emphasis is on ASEAN countries but important developments in the broader Asia-Pacific region are not ignored. The publication seeks to provide readable and easily understood analyses of major political, strategic, economic and social developments within the region.
Keywords: Asian Studies